Factors Influencing the Participation of Informal Workers in Social Employment Security in Indonesia - Sidharta, Rizky Vitiant (Dinasti Publisher, 2026)
This study aims to analyze the factors influencing informal workers' participation in the Employment Social Security program in Indonesia, based on 2022 Susenas data. Participation in employment social security is one effort to improve workers' welfare, but the number of informal workers registered in this program is still relatively low. This study uses a quantitative approach, analyzing data obtained from the Central Statistics Agency (BPS), using the logistic regression method to identify determinants. The results show that demographic factors, employment status, education level, and private insurance participation have a significant influence on informal workers' decisions to participate in the employment social security program. In addition, socioeconomic factors such as type of employment have also been shown to influence participation rates. This study provides recommendations for the government to increase accessibility and awareness of informal workers regarding the importance of employment social security in order to increase social security coverage in Indonesia.